2009
DOI: 10.1186/1472-6963-9-225
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of paediatric prescription drug utilization between the spanish and immigrant population

Abstract: BackgroundThe immigrant population has increased greatly in Spain in recent years to the point where immigrants made up 12% of the infant population in 2008. There is little information available on the profile of this group with regard to prescription drug utilization in universal public health care systems such as that operating in Spain. This work studies the overall and specific differences in prescription drug utilization between the immigrant and Spanish population.MethodsUse was made of the Aragonese He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The results of this study agree with the results of similar studies on the use of hospital services [31][32][33] , consumption of pharmaceuticals 18,20 and the use of PC services 34 in Spain published before. The literature review done by Uiters 24 found a lower rate of visits in the immigrant population, but showed wide variability between studies.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study agree with the results of similar studies on the use of hospital services [31][32][33] , consumption of pharmaceuticals 18,20 and the use of PC services 34 in Spain published before. The literature review done by Uiters 24 found a lower rate of visits in the immigrant population, but showed wide variability between studies.…”
Section: Discussionsupporting
confidence: 92%
“… 29 Our results are in accordance with studies among children in Sweden, the Netherlands and Spain that have shown lower usage of prescribed medications among first generation immigrant children compared to non-immigrants. 5 30–34 …”
Section: Discussionmentioning
confidence: 99%
“…Priority visits were identified based on the triage level established by the Aragon Health Service; out of the five categories listed, levels 1–3 are assigned to priority visits. Prescription drug use was measured as the total annual expense using recommended retail drug prices [ 15 ].…”
Section: Methodsmentioning
confidence: 99%